Fine Mapping of Monoclonal Antibody Epitopes on Human von Willebrand Factor Using a Recombinant Peptide Library - Ginsburg, David; Bockenstedt, Paula L; Allen, Elizabeth A; Fox, David A; Foster, Paul A; Ruggeri, Zaverio M; Zimmerman, Theodore S; Montgomery, Robert R; Bahou, Wadie F; Johnson, Timothy A; Yang, Angela Y (Thrombosis and Haemostasis, 1992)
A recombinant human von Willebrand factor (vWF) cDNA fragment library was constructed in λgtll for the localization of anti-vWF monoclonal antibody epitopes. Twelve of 21 monoclonal antibodies screened identified epitopes expressed in λgtll as β-galactosidase fusion proteins. By sequence analysis, these antigenic determinants were localized to segments ranging from 17 to 105 amino acids in length. Four epitopes apparently shared by more than one antibody were identified, suggesting the presence of immuno-dominant epitopes within vWF. Monoclonal antibody C3, which blocks factor VIII (FVIII) binding to vWF, bound to the same epitope previously identified by a second monoclonal antibody which also blocks this function, suggesting that this region may be at or near the vWF/FVIII binding domain. Three antibodies recognize the same region within the vWF A2 repeat. Mutations near this region appear to be responsible for Type IIA von Willebrand’s disease. The co-localization of these antibodies suggests that this domain might be exposed on the surface of vWF, consistent with its apparent increased sensitivity to plasma proteases.